Exploring the Association Between Air Pollutant Exposure and Krebs von den Lungen-6 (KL 6) Serum Levels in Outdoor and Indoor Workers in Banyumas District, Central Java - Euis Tia Istianah; Nendyah Roestijawati; Joko Mulyanto (Universitas Airlangga, 2022)
Introduction: Indonesia ranks 8th globally in the air pollution index, with poor air quality causing premature deaths from lung ailments such as interstitial lung diseases. Krebs von den Lungen-6 (KL 6) can be used to detect lung disease caused by air pollution. However, the number of studies investigating the link between air pollutant exposure and KL-6 levels is inadequate. The present study explores the association between air pollutant exposure and KL-6 levels in workers in different settings. Methods: This cross-sectional study recruited 70 individuals who were divided into two groups. Dust levels were measured using a particle counter as a proxy for air pollutant levels. KL-6 levels were measured with ELISA. The Spearman correlation test, Mann-Whitney test, and generalized linear model were used in statistical analyses. Results and Discussion: Air pollutant exposure differed significantly between outdoor and indoor settings (p = 0.000). A significant difference was found in KL-6 serum levels between outdoor and indoor workers (p = 0.000). Air pollutant levels were inversely associated with KL-6 serum levels in outdoor (r = -0.557, p < 0.05) and indoor workers (r = -0.360, p < 0.05). Working duration did not significantly correlate with KL-6 serum levels in either group. A tendency of linear association among air pollutant exposure, overall working duration, and KL-6 serum levels was found in the multivariable model. Conclusion: Work settings were associated with varying exposures to air pollutants and KL-6 serum levels. Higher exposure to pollutants may be associated with an increase in KL-6 serum levels.